Israel at sixty : a political and oral history of a nation reborn - Strober, Deborah H. (Deborah Hart), 1940-; Strober, Gerald S. (Hoboken, N.J : John Wiley & Sons, 2008)
"What could celebrate Israel's sixtieth anniversary more apply than a stirring history of the nation told by the people who lived it? Based on extensive interviews, Israel at Sixty presents a balanced, comprehensive account of this complex and amazing land. It re-creates historic events from the actions of Israel's founding visionaries through the ravages of six wars with its Arab neighbors to its growing strength and international stature and efforts to make permanent peace with its adversaries."--BOOK JACKET.
From the rise of Nazism to post-war efforts to establish the modern Jewish state -- Proclamation of the Jewish state and its up-building -- Seismic changes -- New realities -- Can Israel survive?
Includes index.
Keywords: Arab-Israeli conflict; Israel -- History